Bakteriální původci nozokomiálních pneumonií - multicentrická stidie v Ceské republice - Htoutou Sedláková, Miroslava; Pudová, Vendula; Kolář, Milan (Klinicka mikrobiologie a infekcni lekarstvi, 2015)
INTRODUCTION: The objectives were to assess the prevalence of etiologic agents of hospital-acquired pneumonia (HAP) in patients staying in four big hospitals in the Czech Republic and requiring artificial ventilation. The resistance of the isolated pathogens to antibiotics was determined and initial antibiotic therapy was discussed. METHODS: Included in the study were 155 patients with HAP staying from May 1, 2013 to January 31, 2014 in the Departments of Anesthesiology and Critical Care in the following four centers: Thomayer Hospital Prague, University Hospital Brno, University Hospital Hradec Králové and University Hospital Olomouc. From these patients, endotracheal secretion samples were processed using standard microbiology methods. In identified bacterial strains, susceptibility to antibiotics was tested with the microdilution method according to the EUCAST recommendations. Production of ESBL and AmpC beta-lactamases was detected by disk diffusion tests specific for the particular enzymes. ESBL- and AmpC-positive isolates were subjected to basic genetic analysis. RESULTS: Over the study period, a total of 266 isolates were obtained from 140 patients, with 15 patients having negative culture result. Late-onset pneumonia was present in 72 %. Gram-negative bacteria were most prevalent (81 %), namely Pseudomonas aeruginosa, Klebsiella pneumoniae and Escherichia coli. Phenotypic tests for production of broad spectrum beta-lactamases were positive in 37 % of Enterobacteriaceae. Genes for CTX-M, SHV, TEM beta-lactamases or CIT and DHA types of AmpC enzymes were detected. No carbapenemase-producing bacteria, methicillin-resistant Staphylococcus aureus or vancomycin-resistant enterococci were detected. CONCLUSION: The study showed that HAP in the Czech Republic was mostly of Gram-negative etiology. Variable antibiotic susceptibility in the two most frequent etiological agents (Pseudomonas aeruginosa and Klebsiella pneumoniae) resulted in severe therapeutic difficulties. A total of 49 % of patients received inadequate therapy. This fact suggests the impact of antibiotic resistance on intensive care patients´ survival or death. Our study confirmed that one in three patients dies because of HAP.
Keywords: Female; ženské pohlaví; lidé; bakteriální pneumonie; Anti-Bacterial Agents; Pneumonia, Bacterial; Cross Infection; bakteriální léková rezistence; Male; Aged; Bacteria; Czech Republic; infekce spojené se zdravotní péčí; Česká republika; senioři; mužské pohlaví; antibakteriální látky; Drug Resistance, Bacterial; Humans